DNA topoisomerase II alpha promotes the metastatic characteristics of glioma cells by transcriptionally activating β-catenin. Issue 2 (1st February 2022) - Liu, Yi; Ma, Jun; Song, Jiu-Shan; Zhou, Hai-Ying; Li, Jing-Hui; Luo, Cheng; Geng, Xin; Zhao, He-Xiang
ABSTRACT: DNA topoisomerase II alpha (TOP2A) reportedly plays a crucial role in several cancers, however, the precise regulatory role of TOP2A in metastatic characteristics of glioma is still poorly understood. Herein, we sought to elucidate the mechanisms by which TOP2A affects the metastatic phenotypes of glioma. We observed that a high level of TOP2A expression was dramatically linked with inferior survival in glioma patients while silencing of TOP2A impaired glioma cell proliferation and aggressiveness. TOP2A was found to directly interact with β-catenin and facilitated its translocation into the nucleus. Mechanistically, TOP2A effectively induced glioma cell growth and invasion in a β-catenin-dependent manner. Overall, we pinpoint TOP2A as a critical activator of the Wnt/β-catenin pathway in glioma, promoting cell growth, migration, and invasion.